Genesis colours of kelicap - Shaari, Nazlina (Universiti Putra Malaysia Press, 2015)
The texture, colours and the drape of textiles, provoke a highly personal engagement. Genesis being the epitome of color creation provides the harmonious colour combination in the art. It shows how it was formed and the color changes, evolved, and flowed through the fabric surfaces. The Genesis Colours of Kelicap represents an analysis of colour exploration and transformation of the Kelicap bird species.